Urgent Care: A Valuable New Setting for Training Physician Assistant Students. Issue 1 (21st March 2022) - Addington, Tiffany; Johnson, Jennifer; Montalbano, Amanda
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to assess physician assistant (PA) students' perceptions of using a pediatric urgent care clinic for their pediatric acute care experience. Methods: PA students were surveyed on completion of their pediatric urgent care rotations (June 2017 to March 2020). Positive perception was ≥4 on a 5-point scale or ≥80% on agreement for dichotomous variables. Qualitative question responses were open coded for positive themes and opportunities for improvement. Results: Of the 32 students, 29 (90.6%) completed evaluations. Students reported an overall positive perception: patient care, 4.66 (standard deviation [SD] 0.61); system-based practice, 4.76 (SD 0.44); professionalism, 4.90 (SD 0.31); medical knowledge, 4.90 (SD 0.31); and practice-based learning and improvement, 4.66 (SD 0.61). However, interpersonal and communication skills were rated positively on only 65.5% of the evaluations. Conclusions: An academic pediatric urgent care clinic was regarded positively by PA students as a novel setting to complete a pediatric acute care rotation, but students required more opportunities to work collaboratively.